ANALISIS NILAI BUDAYA TUNGKU TIGO SAJARANGAN DALAM MANAJEMEN PENDIDIKAN SEKOLAH DASAR - Fauziah, Yuhardina; Fauziah, Muhardila; Putri, Malysa Harteva; Nurizka, Rian (Refleksi Edukatika : Jurnal Ilmiah Kependidikan, 2024)
The aim of this research is to analyze Tigo Tungku Sajarang's cultural values in leadership in elementary schools.The method used is descriptive qualitative analysis. Data analysis was carried out descriptively qualitatively, namely reducing data, presenting data and conclusions. Data collection techniques using interviews, observation and documentation.The results of this research show that there are Tigo Tungku Sajarangan cultural values in the leadership carried out in elementary schools by school principals, teachers and student guardians (school committee).